The Mechanisms of Literary Translation in the Translation of “امشب اشكی میریزد” from Persian to Kurdish according to the Theories of (Vinay) and (Darbelnet) (Raparin Journal of Humanities (RJH), 2024)
Literary translation is a sophisticated and tactful process that exceeds the mechanism of what to say to how to say it from linguistic, cultural and educational perspectives and accommodating these in the target language. This relates to the fact that the literary text is itself the product of interrelated socio-political, economical and religious aspects. Additionally, the literary text is a reflection of the cultural concerns of a society that it represents as well as the emotional and ideological anxieties of the individuals that are also partly the anxieties of the writers. This means that such characteristics give literary text individual and unique qualities which in turn require individual and unique processes of translation especially in the way in which each text is read, evaluated and received.                                                                      In this concern, the theory and mechanism of translation play an active and significant role. Based on this, the translation of the Persian novel “امشب اشكی میریزد” written by Koros Babayi into Kurdish “ئەڤ شەڤە ڕوندكەك دێ ڕژیت”, Tonight a Tear will be Dropped, by Nishtiman M. Saleem in 2011, has been selected to analyzed in relation to the translation mechanisms of the two French theorists Jean Darbelnet (1904-1990) and Jean-Paul Vinay (1910-1999). In his translation of the aforementioned text, the translator has adopted direct translation, or word-for-word translation. Employing this mechanism has assisted the translator in transforming the novel into the target language adding his unique style. However, the translator’s lack of experience in the implementation of the (translation by omission) in which the translator, unable to find equivalents from target language for certain parts of a text in source language, makes omissions in the text. This has caused a number of negative impacts on the text. These have been explained with examples.